Development and Validation of a Stability-Indicating HPLC Method for the Assay of Carvedilol in Pure and Tablet Dosage Forms - Ahmed, Sofia; Khan, Anam; Sheraz, Muhammad A.; Bano, Rehana; Ahmad, Iqbal (Current Pharmaceutical Analysis, 2018)
Background: Carvedilol (CD) is a β-blocker drug that is used in the treatment of hypertension, coronary diseases, etc. The official methods for the assay of CD in British Pharmacopoeia (BP) and United States Pharmacopeia (USP) include potentiometric titration and HPLC analysis, respectively. There are two different methods reported in the USP; one is for the pure CD and the other is for its tablet dosage forms. Both methods are time consuming, require stringent preparation and have specific requirements such as temperature. Objective: The present study involves the development and validation of a simple, rapid and economical, stability-indicating RP-HPLC method for the assay of CD in pure and tablet dosage forms. Method: A mobile phase of acetonitrile and water in a ratio of 60:40, v/v, has been used for the assay of CD at pH 2.5 giving the retention time (tR) of around 3 min. The method has been validated according to the guidelines of International Council for Harmonization (ICH) for parameters such as linearity, range, accuracy, precision, sensitivity, robustness and specificity. Results: The results indicate that the method is linear in the range of 25-150% (6.25-37.50 μg/ml), highly accurate (100.1%), precise (<1%), robust (<1.5%) and statistically comparable to the official USP methods. Conclusion: The stress degradation studies yielded a number of degradation products with varying tR values, all different from the principle peak of CD thus indicating that the method is highly specific and reliable for the assay of CD.
Keywords: USP method